The impact of intermittent fasting during Ramadan on psychomotor and cognitive skills in adolescent athletes - Bougrine, Houda; Chalghaf, Nasr; Azaiez, Chiraz; Hammad, Ayat S; Boussayala, Ghada; Dhahri, Moez; Henchiri, Hamdi; Al-Saedi, Ali Ibrahim Abd Ulwahid; Al-Hayali, Mazin Dawood Ahmed; AL-Rubaiawi, Ahmed Wateed Mazyed Shdr; Ezzi, Ahmed Farooq Tawfeeq; AL-Sadoon, Nabee Muttlak Nasser; et al. (Frontiers in Sports and Active Living, 2024)
Introduction Intermittent fasting (IF) represents a dietary intervention similar to caloric restriction, characterized by the strategic limitation of food consumption. Among the diverse array of practices for IF, Ramadan IF (RIF), a religious observance in Islam, mandates that healthy adult Muslims abstain from both food and drinks during daylight hours. In sports, researchers have extensively studied IF effects on health, including sleep and physical performance, but its impact on cognitive functions during RIF remains understudied. Therefore, this study was conducted to evaluate the influence of RIF on psychomotor and cognitive performance among young female athletes. Methods To achieve this purpose, a cohort of 23 female handball players, aged 17.2 ± 0.5 years, participated in a series of six testing sessions: one conducted prior to Ramadan (R0), and others during the first (R1), second (R2), third (R3), and fourth (R4) weeks of Ramadan, followed by a session in the week after Ramadan (R5). Each session involved assessments using a Simple Reaction Time Test (SRT), Choice Reaction Time Test (CRT), Vigilance Test (VT), and Mental Rotation Test (MRT). Additionally, dietary intake, body composition, and Pittsburgh Sleep Quality Index (PSQI) scores were evaluated during these periods. Results and discussion The obtained data illustrated that there was a decrease in SRT, CRT, VT, and MRT performances during R1 in comparison to R0 (all p < .001). This reduction was also observed in R2, R3, R4, and R5. Notably, during the fourth week of Ramadan (R4), these cognitive and psychomotor parameters were significantly lower than during the earlier weeks (R1, R2, R3; all p < .001). Furthermore, a gradual decrease in total PSQI scores, sleep quality, and sleep duration was observed throughout the Ramadan period, reaching the lowest levels during R4. These findings illustrate that RIF has a significantly detrimental impact on neuromuscular and cognitive abilities as well as sleep quality in young female athletes. The study also highlights a fluctuating pattern in cognitive function across the four weeks of Ramadan, with the most pronounced decline observed during the final week of fasting illustrating the importance of conducting similar studies on normal individuals from both genders with larger sample size.